2014
DOI: 10.1182/blood-2012-12-473439
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic mouse model demonstrating the oncogenic role of mutations in the polycomb-group gene EZH2 in lymphomagenesis

Abstract: Key Points• A functional demonstration of the oncogenic role of mutated EZH2 in a mouse model is presented.• The global effects of mutated EZH2 on expression and epigenome have been characterized.The histone methyltransferase EZH2 is frequently mutated in germinal center-derived diffuse large B-cell lymphoma and follicular lymphoma. To further characterize these EZH2 mutations in lymphomagenesis, we generated a mouse line where EZH2 Y641F is expressed from a lymphocyte-specific promoter. Spleen cells isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 43 publications
0
39
0
2
Order By: Relevance
“…Monoallelic mutations that result in substitution of Y641 within the SET domain of EZH2 lead to increased conversion of H3K27me1 to H3K27me2 (H3K27 dimethylation) and H3K27me3 and have been identified in 22% of patients with germinal center diffuse B-cell lymphoma . Transgenic mouse models initially demonstrated that a specific overexpression of EZH2 Y641F/N in lymphocytes is insufficient for lymphomagenesis on its own but can cooperate with Bcl2 or Myc overexpression (Beguelin et al 2013;Berg et al 2014). These studies suggested that the carcinogenic activity of EZH2 Y641 mutations rely on other oncogenic events to drive malignant transformation.…”
Section: Polycomb Group (Pcg) Proteins In Normal and Malignant Hematomentioning
confidence: 99%
“…Monoallelic mutations that result in substitution of Y641 within the SET domain of EZH2 lead to increased conversion of H3K27me1 to H3K27me2 (H3K27 dimethylation) and H3K27me3 and have been identified in 22% of patients with germinal center diffuse B-cell lymphoma . Transgenic mouse models initially demonstrated that a specific overexpression of EZH2 Y641F/N in lymphocytes is insufficient for lymphomagenesis on its own but can cooperate with Bcl2 or Myc overexpression (Beguelin et al 2013;Berg et al 2014). These studies suggested that the carcinogenic activity of EZH2 Y641 mutations rely on other oncogenic events to drive malignant transformation.…”
Section: Polycomb Group (Pcg) Proteins In Normal and Malignant Hematomentioning
confidence: 99%
“…Ezh2 has also been found to play an oncogenic role in lymphoma and AML. A recent study showed that Ezh2 Y641F , which is detected as a gain-of-function mutation in FL and DLBCL, strongly promotes the development of lymphoma in mice by collaborating with c-Myc [87]. Ezh2 is believed to be important in leukemogenesis because, loss of Ezh2 decreases the proliferative ability of leukemia cells and induces differentiation, delaying the onset of AML induced by the MLL-AF9 fusion gene in mice [88,89].…”
Section: Prc2 Members In Hematological Malignanciesmentioning
confidence: 99%
“…[10][11][12][13] Extensive evidence has linked PRC2 deregulation to malignant hematopoiesis. Recurrent EZH2 gain-offunction mutations were found in germinal center B-cell lymphoma patients, 14,15 and constitutive expression of wild-type or lymphomaassociated mutant EZH2 in hematopoietic lineages induced myeloproliferative diseases 16 and lymphomagenesis, 13,17 respectively, in murine models. Furthermore, EZH1 compensates the function of EZH2 9,18 and emerges as regulator of myeloid neoplasms.…”
Section: Introductionmentioning
confidence: 99%